PRIMORDIALISME DALAM PEMILIHAN BUPATI DAN WAKIL BUPATI KABUPATEN KOTAWARINGIN BARAT PERIODE 2017-2022 - Anyualatha Haridison; Edha Romadatama (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2021)
Until this is still a lot of people who choose a candidate leader based on ethnic or religious. Thus the formulation of this research problem is how the behavior of the electorate of the South Arut Subdistrict in the election of Regent and Vice Regent period 2017-2022 in West Kotawaringin regency, and what factors encourage the people of South Arut Subdistrict to behave primordially in the election of Regent and Vice Regent West Kotawaringin period 2017-2022. The purpose of this research is to know and analyze the behavior of choosing primordial of South Arut Subdistrict in the election of Regent and Vice Regent of Kotawaringin Barat period 2017-2022. The research type is qualitative with descriptive approach. Data collection techniques using interview and documentation techniques. Data analysis conducted is qualitative data analysis with descriptive approach. The results showed that the people of South Arut in Kotawaringin Barat District in the election of regional heads became primordial voters because of the strong ethnic and religious influence inherent in the community. The researcher recommends that the people of South Arut should be able to meet the election in accordance with the supposed and select the candidate for the quality. In order to create a better government for West Kotawaringin later. Keywords: Primordialism, Primordial Voters